The new sporting Cold War: implications of the Russian doping allegations for international relations and sport - Altukhov, S.; Nauright, J. (Sport in Society: Cultures, Commerce, Media, Politics, 2018)
This article examines current state of the new sporting cold war in the world of sports. It provides an examination of the 2014-2018 Russian doping scandal. Political and ideological prerequisites that triggered this scandal are considered, and based on obtained observations, an analysis of possible scenarios in the development of events is made as are recommendations for future progress in ending this unnecessary neo-cold war.